The return of the Charlie Monsters - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2014)
When a turkey debacle endangers his relationship with Sally May and a case of poisoning almost kills him, Hank must figure out who might be his mortal enemy.